Curable Layered Double Hydroxide Nanoparticles‐Based Perfusion Contrast Agents for X‐Ray Computed Tomography Imaging of Vascular Structures. Issue 2 (1st December 2021) - Tokudome, Yasuaki; Poologasundarampillai, Gowsihan; Tachibana, Koki; Murata, Hidenobu; Naylor, Amy J.; Yoneyama, Akio; Nakahira, Atsushi
Abstract : Imaging complex vascular structures by X‐ray microcomputed tomography (μ‐CT) is becoming vital for research purposes in pathology of vascular diseases. Acrylic‐based polymerizable resins are widely adopted for the contrast agent to prepare pathological specimens for imaging of vascular structures. For imaging of vascular structures at higher resolution, it is promising to develop inorganic‐type contrast agents with higher X‐ray attenuation coefficient as well as low viscosity, homogeneity, minimum shrinkage, curable (gellable) for replication, and low cost. Herein, a novel inorganic sol–gel system based on concentrated colloidal dispersion of NiAl layered double hydroxide (LDH) nanoparticles is described, allowing imaging of vascular structures at high resolution. NiAl LDH acts as nanofiller and alkaline catalyst to form a silica/LDH monolithic material with homogeneity from the nanoscale. Moreover, NiAl LDH nanoparticles contribute to the strong enhancement of the X‐ray attenuation. As a proof‐of‐concept, X‐ray μ‐CT imaging of the developed contrast agent in glass capillaries and of blood vessels of a human placenta and murine liver is demonstrated. Abstract : A curable contrast agent based on layered double hydroxide (LDH) nanoparticles is developed for X‐ray computed tomography (CT) imaging. The contrast agent can be prepared though an easy reaction and exhibits low viscosity, high homogeneity, and high X‐ray attenuation. High‐resolution X‐ray microcomputed tomography (μ‐CT) imaging of complex vascular structures becomes possible without maceration process.